ANALISIS DAMPAK DAN KEBIJAKAN PERDAGANGAN INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI - Tria Ma’rifaturrohmmah; Putri Aruf Mumtaz; Hikmah Tul Rima (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
Economic growth is an important indicator in measuring the progress of a country, which is influenced by various factors, one of which is international trade. This study aims to analyze the impact of international trade on Indonesia's economic growth. The method used is a descriptive method through literature studies and secondary data. The results of the study show that international trade has a positive impact, such as increasing state revenue, creating jobs, and strengthening international relations. However, there are also negative impacts, including economic dependence, unhealthy competition, and decreasing the competitiveness of local industries. In addition, international trade policies play an important role in mitigating these negative impacts. With the right strategy, Indonesia can maximize the benefits of international trade to support sustainable economic growth.